Spirit of Creativity during the Pandemic Perspective of Al-Azhar and An-Nuur: Study QS. Al-Baqarah (2): 219-220 - Reza Firmansyah; Ecep Ismail (UIN Sunan Gunung Djati Bandung, 2021)
This paper aims to discuss the spirit of creativity in the pandemic period from the perspective of Tafsir Al-Azhar and An-Nuur. The method used in this paper is a type of qualitative research through literature study using content analysis. The results and discussion of this paper include the spirit of creativity in the pandemic period in the Qur'an as well as the perspectives of Al-Azhar and An-Nuur interpretations. This paper concludes that creativity is the key to surviving a pandemic. As one of the foundations is QS Al-Baqarah (2) at the end of verse 219 and the beginning of verse 220. The wisdom from the interpretation of Hamka and Hasbie Ash-Shiddiqie shows this verse to the spirit of creativity in any condition, especially during a pandemic. So that it can still be of worship value and have an impact on the benefit of others and together.